If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-4p-3(3-4p)=4(p-3)-13
We move all terms to the left:
-4p-3(3-4p)-(4(p-3)-13)=0
We add all the numbers together, and all the variables
-4p-3(-4p+3)-(4(p-3)-13)=0
We multiply parentheses
-4p+12p-(4(p-3)-13)-9=0
We calculate terms in parentheses: -(4(p-3)-13), so:We add all the numbers together, and all the variables
4(p-3)-13
We multiply parentheses
4p-12-13
We add all the numbers together, and all the variables
4p-25
Back to the equation:
-(4p-25)
8p-(4p-25)-9=0
We get rid of parentheses
8p-4p+25-9=0
We add all the numbers together, and all the variables
4p+16=0
We move all terms containing p to the left, all other terms to the right
4p=-16
p=-16/4
p=-4
| 8+5x=4x+11 | | -5t=9-6t | | 3(2d-1)=3 | | 7+3x=2x+17 | | 6×√x=12 | | 8+10c=-4+7c | | 20-y=12+5y | | x(2x-3)+3(x+x2)=45 | | 5(3h-6)=60 | | 6(5x+1)=+1)=5x-9x | | 12/m=75/40 | | 2^x/3^(-x)=36 | | (6x-12)^2-36=0 | | 9(8-x)=-108 | | 6(4x+1)=+1)=5x-7x | | t4+3=12 | | 11a=5 | | 5j-16=6+3 | | 5(4)+y=3(4)+5y | | 8x+-8=6x+14 | | 8x-2(3-2x)=3(x-4)-39 | | 4(1-3n)=36-4n | | 8x+x=8x-6 | | 3x5-5=2x | | -5/3(x+2)=35/2 | | -2f+9=f-6+2f | | 2(3x)=40.8 | | 5=20-c | | 19d=12+20d | | 11w+18w-6+2=-3w+2-6 | | 2(n+9)=6(n-5)+8 | | 10+12y=7 |